Overexpression of SbMyb60 in Sorghum bicolor impacts both primary and secondary metabolism. Issue 1 (25th September 2017) - Scully, Erin D.; Gries, Tammy; Palmer, Nathan A.; Sarath, Gautam; Funnell‐Harris, Deanna L.; Baird, Lisa; Twigg, Paul; Seravalli, Javier; Clemente, Thomas E.; Sattler, Scott E.
Summary: Few transcription factors have been identified in C4 grasses that either positively or negatively regulate monolignol biosynthesis. Previously, the overexpression of SbMyb60 in sorghum ( Sorghum bicolor ) has been shown to induce monolignol biosynthesis, which leads to elevated lignin deposition and altered cell wall composition. To determine how SbMyb60 overexpression impacts other metabolic pathways, RNA‐Seq and metabolite profiling were performed on stalks and leaves. 35S::SbMyb60 was associated with the transcriptional activation of genes involved in aromatic amino acid, S ‐adenosyl methionine (SAM) and folate biosynthetic pathways. The high coexpression values between SbMyb60 and genes assigned to these pathways indicate that SbMyb60 may directly induce their expression. In addition, 35S::SbMyb60 altered the expression of genes involved in nitrogen (N) assimilation and carbon (C) metabolism, which may redirect C and N towards monolignol biosynthesis. Genes linked to UDP‐sugar biosynthesis and cellulose synthesis were also induced, which is consistent with the observed increase in cellulose deposition in the internodes of 35S::SbMyb60 plants. However, SbMyb60 showed low coexpression values with these genes and is not likely to be a direct regulator of cell wall polysaccharide biosynthesis. These findings indicate that SbMyb60 can activate pathways beyond monolignol biosynthesis, including those that synthesize the substrates and cofactors required for lignin biosynthesis.